Experimental Testing Comparison between Wiremesh Reinforcement and Plain Reinforcement on Concrete Slabs - Rasidi, Nawir; Dora, Margaritha P.I; Ningrum, Diana (Asian Journal Science and Engineering, 2022)
The demand for building quality in the construction of structures is a major requirement. One part of the structure is the floor slab work. The main obstacle is when the floor slab is loaded there will be deflection and bending moment. Meanwhile, there are demands for shorter work times at lower costs. This study aims to analyze the concrete slab against the flexural strength test, compressive strength test and tensile strength test of plate reinforcement. In this study, plate reinforcement used plain steel with a diameter of 6 mm and 8 mm. Then the plain iron reinforcement plate was compared with the M6 ??and M8 wiremesh reinforcement plates. The results showed that the flexural strength test for plain iron reinforcing plates with a diameter of 6 mm was 45000 Kg.cm, while for a concrete slab with wiremesh M6 reinforcement it was 42500 Kg.cm then for reinforcement with a diameter of 8 mm it was 32500 Kg.cm while wiremesh M8 was 57500 Kg. .cm. This shows that the concrete slab with wiremesh reinforcement is better able to accept the load, as well as better moment capacity in bending, compressive and tensile tests compared to conventional slabs. Keywords: Concrete Slabs, Wiremesh Reinforcement, Plain Reinforcement